Development of Vestibular Stability of Children in Physical Education Lessons: Life Sciences-Psychology for Curing Mental Health - Polevoy, Georgiy (International Journal of Life Science and Pharma Research, 2022)
The problem of the influence of physical activity of schoolchildren on their mental processes is promising and little studied. The aim is to determine the influence of physical activity in physical education lessons on the vestibular stability indicators of schoolchildren. The main objectives of the study are to study the problems of children's health, to determine the factors that improve it, to identify the role of physical culture for the health and development of schoolchildren. The study was conducted in a secondary school in Russia, it was attended by ninth graders aged 15-16 years in the number of 141 schoolchildren. The main research method was the “Turns on the gym bench”, which determines the level of vestibular stability development of schoolchildren. The test was used before and after the physical education lesson 1 time per month for 5 months. Children who did not engage in physical education in the lesson were not able to significantly improve their performance in the test, which indicates a possible adaptation to the test after its first performance before the lesson. Children who were engaged in physical exercises were able to significantly increase the test results. The results obtained determine the effectiveness of the influence of a physical education lesson at school on the indicators of children's vestibular stability. This study will serve as an additional motivation for children to engage in physical culture, since the impact of physical exercises has a positive effect not only on the development of physical qualities, but also on the vestibular stability of schoolchildren.